2003
DOI: 10.1007/s00018-003-3084-x
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the metabolic and molecular basis for diabetic neuropathy

Abstract: Diabetic polyneuropathy is the most common complication of diabetes mellitus. Several interactive pathogenetic mechanisms have been identified mainly in streptozotocin-induced diabetes in rats and have been ascribed to hyperglycemia. Over the last number of years it is becoming increasingly clear that diabetic neuropathy differs in type 1 and type 2 diabetes in humans and in murine models that more accurately mimic the human disorders. Beside hyperglycemia, attention is increasingly being paid to the pathogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
150
1
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(161 citation statements)
references
References 259 publications
(233 reference statements)
5
150
1
5
Order By: Relevance
“…Clinically, painful diabetic neuropathy occurs in patients with pre-diabetes (8,9) and early in the course of diabetic neuropathy in type 2 patients (42,43). This has been linked to deficits in neurotrophic factors such as NGF and impaired insulin action with impacts on neuroeffector peptides like substance P and CGRP (36,38,44). These clinical conditions have been explored experimentally in the glucose-intolerant Stockholm-bred GK rat and in the type 2 diabetic BBZDR/Wor rat (10,12).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, painful diabetic neuropathy occurs in patients with pre-diabetes (8,9) and early in the course of diabetic neuropathy in type 2 patients (42,43). This has been linked to deficits in neurotrophic factors such as NGF and impaired insulin action with impacts on neuroeffector peptides like substance P and CGRP (36,38,44). These clinical conditions have been explored experimentally in the glucose-intolerant Stockholm-bred GK rat and in the type 2 diabetic BBZDR/Wor rat (10,12).…”
Section: Discussionmentioning
confidence: 99%
“…These results are in accordance to Pascoe et al (1997) who demonstrated that diabetes is invariably accompanied by concomitant axonal degeneration that resulted in proximal muscle weakness. Also, in the same line, Sima (2003) suggested that diabetic neuropathy was associated with axonal atrophy.…”
Section: Ajptmentioning
confidence: 87%
“…Peripheral neuropathy is one of the major complains in both types I and II diabetic patients and it is associated with several problems such as cardiovascular defects, retinopathy and muscular pain or weakness (Yamagishi et al, 2008;Sima, 2003;Rajbhandari and Piya, 2005). Since these defects affect the quality and quantity of life, treatment of diabetic neuropathy or prevention of its accompanying symptoms has been considered as a major goal in the recent decades.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral neuropathy is one of the major complains in both types I and II diabetic patients and it is associated with several problems such as cardiovascular defects, retinopathy and muscular pain or weakness (Yagihashi et al, 2007;Sima, 2003;Rajbhandari and Piya, 2005). Since these defects affect the quality and quantity of life, treatment of diabetic neuropathy or prevention of its accompanying symptoms has been considered as a major goal.…”
Section: Discussionmentioning
confidence: 99%